Thermal Observation in Vernacular Dwellings of Gurjakhani, Myagdi, Nepal (Journal of Science and Engineering, 2026)
Indoor air temperature is a key parameter defined by ASHRAE Standard 55 for assessing thermal comfort. Numerous studies have examined thermal comfort conditions in vernacular architecture across different climatic regions. In particular, Dr. Hom Bahadur Rijal and Dr. Sushil Bajracharya, frontiers researchers in this subject have investigated the thermal comfort characteristics of vernacular buildings in high-altitude settlements and Kathmandu valley respectively. This study focuses on the thermal observations of vernacular dwellings in Gurjakhani, Myagdi, Nepal, situated at an elevation of 2638 meters above sea level. The region experiences cool summers, cold winters and occasional snowfall.  The local buildings are primarily constructed with stone masonry bonded with mud mortar, while internal partitions are composed of timber planks. The flooring system consists of timber framing with mud overlay, and roofing materials typically comprise stone slates. The houses vary in height from one to three stories. Field measurements of indoor air temperature and surface temperatures within a designated room were conducted using available electronic sensors. Supplementary meteorological data were obtained from online sources to calculate the operative indoor air temperature. The CEB thermal comfort tool was used for thermal comfort analysis. Findings from the one-week field investigation conducted in October indicate that the indoor environment remains cold relative to the calculated operative temperature, yet demonstrated greater thermal satisfaction compared to the outdoor environment.